2011
DOI: 10.1051/0004-6361/201016193
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the spinning gas and dust in the disc around the supergiant A[e] star HD 62623

Abstract: Context. To progress in the understanding of evolution of massive stars one needs to constrain the mass-loss and determine the phenomenon responsible for the ejection of matter an its reorganization in the circumstellar environment Aims. In order to test various mass-ejection processes, we probed the geometry and kinematics of the dust and gas surrounding the A[e] supergiant HD 62623. Methods. We used the combined high spectral and spatial resolution offered by the VLTI/AMBER instrument. Thanks to a new multiw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(124 citation statements)
references
References 29 publications
9
114
0
1
Order By: Relevance
“…A convincing example of this equatorial mass-transfer was reported for the binary system HD 62623 (Plets et al 1995;Millour et al 2011), an A-type supergiant with a solar-mass companion orbiting with a period P = 137.9 d. The SED and spectra from this system exhibit a large infrared excess and strong emission lines, respectively, and HD 62623 is classified as A[e]/B[e] source. Recent AMBER observations have shown that the Brγ line originates in a dense disk of plasma larger than the orbit of the secondary (Millour et al 2011).…”
Section: Non-conservative Evolution Of the υ Sgr And β Lyr Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A convincing example of this equatorial mass-transfer was reported for the binary system HD 62623 (Plets et al 1995;Millour et al 2011), an A-type supergiant with a solar-mass companion orbiting with a period P = 137.9 d. The SED and spectra from this system exhibit a large infrared excess and strong emission lines, respectively, and HD 62623 is classified as A[e]/B[e] source. Recent AMBER observations have shown that the Brγ line originates in a dense disk of plasma larger than the orbit of the secondary (Millour et al 2011).…”
Section: Non-conservative Evolution Of the υ Sgr And β Lyr Systemsmentioning
confidence: 99%
“…Recent AMBER observations have shown that the Brγ line originates in a dense disk of plasma larger than the orbit of the secondary (Millour et al 2011). The kinematics in the Brγ line is most probably Keplerian, suggesting that most of the mass-transfer occurs in this system close to the orbital plane.…”
Section: Non-conservative Evolution Of the υ Sgr And β Lyr Systemsmentioning
confidence: 99%
“…The mass loss process from L 2 has been discussed in many papers, e.g., Chesneau et al (2014) for a recent paper on V838 Mon, but in many cases for rotating disks rather than expanding ones (e.g., Millour et al 2011;Plets et al 1995). We here discuss only expanding rings/disks that escape from the binary system.…”
Section: Examining Equatorial Mass Lossmentioning
confidence: 99%
“…If spectrally dispersed interferograms are available, the wavelength-differential phases in spectral channels across emission lines can be used to derive phases of the Fourier transform of the object in spectral channels across emission lines (Petrov et al 2007;Schmitt et al 2009;Millour et al 2011;Ohnaka et al 2011Ohnaka et al , 2013Mourard et al 2015). This is possible if the phase of the Fourier transform of the object in the continuum is known (for example, if the continuum object is unresolvable) or can be derived from a continuum image reconstructed from continuum visibilities and continuum closure phases using a closure phase method.…”
Section: Differential-phase and Closure-phase Image Reconstruction Mementioning
confidence: 99%